2012
DOI: 10.1111/j.1744-7402.2012.02759.x
|View full text |Cite
|
Sign up to set email alerts
|

Alumina Toughened Zirconia Nanocomposite Incorporating Al2O3 Whiskers

Abstract: We investigated the Vickers hardness and fracture toughness of an Al2O3(n) + 70 wt% ZrO2 (TZ‐3Y)n nanocomposite with addition of 2.5 wt% Al2O3 whiskers. Densities greater than 95% were reached after conventional sintering at 1500°C. The fracture toughness was increased 62% over pure Al2O3. Microcracking and crack deflection can be the mechanisms responsible to improve the fracture toughness. The use of ATZ composites with a low percent of whiskers can be a promising biomedical material for medical and dental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Studies have also shown that crystalline mullite reacts with water vapor at 1100℃ through the following reaction at grain boundaries. 39 This may lead to degradation of mullite in the ZTA w . Single crystal mullite inclusions should not be affected by this reaction; however, large diameter whiskers formed by the fusion of aligned smaller diameter whiskers may be prone to degradation through reaction (4).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown that crystalline mullite reacts with water vapor at 1100℃ through the following reaction at grain boundaries. 39 This may lead to degradation of mullite in the ZTA w . Single crystal mullite inclusions should not be affected by this reaction; however, large diameter whiskers formed by the fusion of aligned smaller diameter whiskers may be prone to degradation through reaction (4).…”
Section: Resultsmentioning
confidence: 99%
“…Except for these basic forms of ZrO 2 -Al 2 O 3 materials, the shapes of both components could be altered, or other metal compounds could be added, to achieve better toughening effect. Aguilar-Elguézabal and Bocanegra-Bernal (2013) investigated the fracture toughness of an Al 2 O 3 (n)-70 wt% ZrO 2 (ZrO 2 with 3 mol% yttria, TZ-3Y)n nanocomposite with addition of 2.5% Al 2 O 3 whiskers. The fracture toughness was enhanced 62, 28, and 7% over pure Al 2 O 3 , the composite without additions of whiskers, and pure TZ-3Y for medical applications, respectively.…”
Section: Adding Reinforcing Filler As Second Phase To Ceramic Matrixmentioning
confidence: 99%
“…Toughening based on ZrO 2 -Al 2 O 3 system or mica glass ceramics ( Gali and Kumar, 2019 ), and using ion-exchange (chemical methods) tends to preserve excellent esthetics, while adding colorful fillers like AgNPs ( Fujieda et al, 2012 ) would affect ceramic color. For non-esthetic demanding applications, high toughness is the first consideration, which is fine achieved by fiber/whisker-shape ( Aguilar-Elguézabal and Bocanegra-Bernal, 2013 ) or nanocarbon adding ( Siddiqui et al, 2018 ).…”
Section: Current Challenges and Future Outlookmentioning
confidence: 99%
“…[3] To overcome this problem, various strategies and processing approaches have been proposed. [9,10] Carbon fillers, such as carbon nanotubes (CNTs) and carbon fibers have been extensively studied as strong reinforcements due to their remarkable Young's modulus. [9,10] Carbon fillers, such as carbon nanotubes (CNTs) and carbon fibers have been extensively studied as strong reinforcements due to their remarkable Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Among them, the addition of secondary strong and tough nanofillers has become popular for a significant improvement in the mechanical properties of the ceramic matrices can be achieved by introducing a small percentage of these nanofillers. [9,10] Carbon fillers, such as carbon nanotubes (CNTs) and carbon fibers have been extensively studied as strong reinforcements due to their remarkable Young's modulus. However, the high cost of these carbon fillers make them less competitive when mass production of related composites is considered.…”
Section: Introductionmentioning
confidence: 99%